Wideband frequency reconfigurable metamaterial antenna design with double H slots - Adamu Y. Iliyasu; Mohamad Rijal Hamid; Mohamad Kamal A. Rahim; Mohd Fairus Mohd Yusoff; Murtala Aminu- Baba; Mohammed Mustapha Gajibo (Institute of Advanced Engineering and Science, 2020)
This paper presents the design of wideband frequency reconfigurable metamaterial antenna with double H slots. The design is based on the idea of composite right/left-handed transmission line (CRLH-TL) technique. Bandwidth enhancement was achieved by utilizing series left-handed capacitor CL transmission line parameter. The design has several outstanding advantages which include efficient bandwidth to cover many lower Application bands with multi frequency operation characteristics. A comprehensive analysis and simulation were done by using computer simulation technology (CST) software to determine the performance and efficiency of the proposed antenna. From the result obtained, the antenna aquired bandwidth range which covered (2.3-5.2) GHz which is equivalent to 77% fractional bandwidth. The wideband antenna was reconfigured by using frequency reconfiguration technique. From the reconfiguration results, the antenna can be switch from wideband to two single bands which resonate at 2.4 GHz and 4.2 GHz and to dual band which resonate at 2.4 GHz and 4.2 GHz. The realized peak gain at 2.4 GHz is 2.28 dBi and 2.58 dBi for E and H field respectively. The maximum efficiency of 96% was obtained. The antenna can be use for WLAN, proposed lower 5G band and cognitive radio system for frequency sencing.